2019
DOI: 10.15520/jmbas.v7i2.178
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With The One Day Cataract Surgery

Abstract: J o u r n a l o f M e d i c a l B i o m e d i c a l A n d A p p l i e d S c i e n c e s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Meanwhile, research conducted by Stefanija Kalocko found that patient satisfaction was obtained when they receive quality and relevant information (Kolačko, 2019). Being ready to serve twentyfour hours is one form of responsiveness of midwives in serving patients to have consultations.…”
mentioning
confidence: 99%
“…Meanwhile, research conducted by Stefanija Kalocko found that patient satisfaction was obtained when they receive quality and relevant information (Kolačko, 2019). Being ready to serve twentyfour hours is one form of responsiveness of midwives in serving patients to have consultations.…”
mentioning
confidence: 99%